Implementasi Transparansi Harga sebagai Bagian dari Tata Kelola Usaha dalam Meningkatkan Kepuasan Pelanggan Barbershop - Dedi Anggara (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
Business governance refers to the way a business is managed in a structured, transparent, and accountable manner to achieve its objectives. Price is one of the key elements in determining customer satisfaction. Clear pricing information influences customers’ perceived value, which ultimately impacts their level of satisfaction. Abstract This study aims to analyze the implementation of price transparency as part of business governance and its impact on customer satisfaction in MSME barbershops. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation. The informants consist of business owners, employees, and customers. The findings reveal that price transparency has begun to be implemented; however, it is not yet applied consistently. Customers generally have positive perceptions of price transparency, as it enhances trust and provides a sense of comfort. Furthermore, price transparency plays a significant role in improving customer satisfaction by reducing uncertainty, increasing trust, and creating a more positive service experience. This study confirms that price transparency is a crucial element of customer-oriented business governance in the MSME service sector.